Erros de grafia em produções de alunos do ensino médio: análise e reflexões - Sella, Poliana (2017)
The teaching of written language in our schools has shown inefficiency in managing with the spelling difficulties of the students. Teachers engage themselves in teaching spelling rules to their students; however, the errors have been perpetuated until university, in other words, in all the levels of education. Spelling, created to nullify the representation of language varieties and improve the stabilization of the writting, represents a large difficulty to many speakers. It is due to the phonetic-graphic character of the Portuguese language, which is based on various phonetic and phonological factors, spelling code, etymology of the words, patterns, and some special cases. Besides the difficulties with the linguistic code mastery and spelling conventions, many pupils encounter difficulties to realize the sounds of the speech and the phonetic principles that determine their representation in writing, which makes high the incidence of spelling errors originated by the transposition of speech for writing. Based on this assertion, the question we intend to answer with this research is: Which are the origins of the most common spelling errors in textual productions of students in 10th and 11th grades? From the classification of the errors, our purpose is to explore the role of phonetics, and, mainly phonology in the comprehension and apprehension of the spelling rules, in the studied group. Our main objective is reflect about spelling errors of students of the first and second years of high school (10th and 11th grades) of a public school in Southwest Paraná State. This research is based on theoretical assumptions of Applied Linguistics (AL), supported by authors like Bortoni-Ricardo (2005, 2006), Mollica (2003), Cagliari (1999), Oliveira (2005) and Tenani (2011, 2013). This study is framed as an interpretative, qualitative and quantitative research, besides being an ethnographic study too. The data collect occurred in two school classes, one first years and one second year of high school of a public school in a town in the Southwest of Paraná State. Almost all the students from the first year class researched form the second year class, because the intention is to evaluate the development, or not, after working phonetics and phonology with the students. We selected a production per student in each class, taken in the first term of the school year in 2015, and in the last term of the school year in 2016, reaching 55 productions. We applied a questionnaire too, with words and pseudowords, in the last term of 2016. The results indicate that spelling errors related to phonetic-phonological principles and phonological processes outweigh the errors arising from the exclusive spelling convention breaks, suggesting the need to develop greater phonetic-phonological awareness besides the reflection about the language and the patterns it has.